Patterns of Workplace Innovation in Canada - Long, Richard (Relations industrielles / Industrial Relations, 1989)
This paper reports the results of a large-scale Canadian survey of nine types of workplace innovation — profit sharing, gain sharing, pay for knowledge, job sharing, job enrichment, semi-autonomous work groups, quality circles, labour management committees, and 'other' joint problem solving groups. The paper assesses the incidence ofeach type, patterns of implementation, survival rates, and trends over time.